PENGARUH DISIPLIN KERJA DAN LINGKUNGAN KERJA FISIK TERHADAP KINERJA PEGAWAI PUSAT PERENCANAAN PENGEMBANGAN SUMBER DAYA MANUSIA (PPSDM) KEMENTERIAN KEHUTANAN JAKARTA PUSAT - Ratna Safitri; Ahmad Syukri (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2025)
This study aims to determine the effect of work discipline and physical work environment on employee performance at the Human Resources Development Center (PPSDM) of the Ministry of Forestry, Central Jakarta. This study uses a descriptive quantitative method with a population and sample of 56 people. Data analysis techniques used are descriptive statistical analysis, data instrument testing, classical assumption testing, quantitative analysis, and hypothesis testing. The results of the study indicate that work discipline has a positive and significant effect on employee performance with a contribution of 74.6%, while the physical work environment has a positive and significant effect with a contribution of 67.2%. Simultaneously, work discipline and the physical work environment have a positive and significant effect on employee performance by 76.9%. The multiple linear regression equation obtained is Y = 5.687 + 0.602 (X1) + 0.277 (X2). This means that employee performance even without the influence of work discipline and the physical work environment already has an influence of 5.687. Work discipline and the work environment simultaneously have a positive and significant effect on employee performance. This is evidenced by the calculated F value > F table, which is (38.352 > 3.172) with a significance value of 0.05 (0.000 < 0.05). Therefore, Ho is rejected and H3 is accepted. This means that there is a positive and significant influence between work discipline and the physical work environment on employee performance simultaneously at the Human Resources Development Center (PPSDM) of the Ministry of Forestry, Central Jakarta.